A new human leukocyte antigen‐A allele, HLA‐A*02:482. Issue 2 (6th June 2014) - Zhu, X.; Yang, T.; Yao, F.; Che, Z.; Su, P.; Luo, Z.; Tan, R.
<x xml:space="preserve">Abstract</x> A novel allele HLA‐A*02:482 differs from the closest allele HLA‐A*02:01:01:01 by a nucleotide change at codon 57.